2022
DOI: 10.1038/s41467-022-33558-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the spatial chromatin organization and dynamic epigenetic landscapes of macrophage cells during differentiation and immune activation

Abstract: Immunocytes dynamically reprogram their gene expression profiles during differentiation and immunoresponse. However, the underlying mechanism remains elusive. Here, we develop a single-cell Hi-C method and systematically delineate the 3D genome and dynamic epigenetic atlas of macrophages during these processes. We propose “degree of disorder” to measure genome organizational patterns inside topologically-associated domains, which is correlated with the chromatin epigenetic states, gene expression, and chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…The loss of these TF interactions in old age and enriched CTCF binding suggest that aging may promote alterations in the formation and stability of extruded loops. This result is consistent with increased average distance between significant contacts or increased degree of disorder (Lin et al, 2022 ) in old age. As a consequence of loop dysregulation in old age, interactions between promoters and their concomitant regulatory elements are modified, driving alterations in TF binding and the affinity of distal regulatory elements for their target genes and associated expression levels.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The loss of these TF interactions in old age and enriched CTCF binding suggest that aging may promote alterations in the formation and stability of extruded loops. This result is consistent with increased average distance between significant contacts or increased degree of disorder (Lin et al, 2022 ) in old age. As a consequence of loop dysregulation in old age, interactions between promoters and their concomitant regulatory elements are modified, driving alterations in TF binding and the affinity of distal regulatory elements for their target genes and associated expression levels.…”
Section: Discussionsupporting
confidence: 85%
“…For example, genes related to cell cycle regulation ( Anapc1/4, Cdc25a, Mcm6, Prim2 ) and lipid metabolism ( Acly, Ipmk, Sgms2, Aasdh, Pik3c3, Pi4k2b ) were encompassed by TADs with strong intra‐TAD connectivity (top 20%) in both young and aged MuSCs, but showed significantly upregulated gene expression in young MuSCs compared to aged. In further support of this observation, we observed that the average distance between significant contacts within each TAD (degree of disorder (Lin et al, 2022)) increased with age, indicating decreased cooperation between transcription regulatory complexes (Figure S2P). Summing these results indicate that in aged MuSCs, TADs self‐interact in a stronger manner and alter TAD boundaries (Barrington et al, 2019), but chromatin folding within aged TADs is less organized and unable to drive coherent changes in gene expression.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Instead, the E-33 enhancer targeted DDX39B gene located upstream of the TNF gene, whereas the E+85 enhancer targeted C6orf47 and GPANK1 located downstream of the TNF gene. We analyzed the published Hi-C data (GEO: GSE103477) (26,27) and found that high levels of interaction between TNF E-16, E-7.1, and PE in matured THP-1 cells under both resting and IFNβ-stimulated conditions. Although the chromatin capture assay is informative in determining enhancer and core promoter interactions (20), our investigation showed that in situ enhancer deletion is the most effective way to determine which enhancers target the TNF gene and the contribution of enhancers to TNF gene transcription.…”
Section: Discussionmentioning
confidence: 99%